2021
DOI: 10.3389/fmicb.2021.660368
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Application of Molecular Markers and Community-Based Microbial Source Tracking Methods for Identification of Fecal Pollution in River Water During Dry and Wet Seasons

Abstract: It is important to track fecal sources from humans and animals that negatively influence the water quality of rural rivers and human health. In this study, microbial source tracking (MST) methods using molecular markers and the community-based FEAST (fast expectation–maximization microbial source tracking) program were synergistically applied to distinguish the fecal contributions of multiple sources in a rural river located in Beijing, China. The performance of eight markers were evaluated using 133 fecal sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Traditional MST methods have limitations in distinguishing different host species from contamination sources. In this study, the fecal microbiomes were distinguishable by different host groups, as reported in many other studies [39,40]. The machine learning models constructed in this study showed nearly 100% accuracy in predicting host groups based on fecal microbial community structures.…”
Section: Discussionsupporting
confidence: 82%
“…Traditional MST methods have limitations in distinguishing different host species from contamination sources. In this study, the fecal microbiomes were distinguishable by different host groups, as reported in many other studies [39,40]. The machine learning models constructed in this study showed nearly 100% accuracy in predicting host groups based on fecal microbial community structures.…”
Section: Discussionsupporting
confidence: 82%
“…The proportion of each sink community that did not match the signature of the sources included in our analysis was assigned to unknown sources. Such analysis is used to identify potential contamination of the sinks by other unidentified microbial sources (Liang et al, 2021;Shenhav et al, 2019). In our study, ultra-filtration did not only lead to an increase of the relative proportion of stream communities in periphyton, but also to an increased proportion of these unknown sources.…”
Section: Tablementioning
confidence: 52%
“…The authors used cutting edge data handling methods, including statistical methods to account for the large proportion of nondetects, and an estimation of spatial and temporal variations of same-host contribution using ratios between given Bacteroidales MST markers and a general Bacteroidales marker (Bambic et al 2015 ). Separating the sample set into dry and wet periods allowed Liang et al ( 2021 ) to reveal differing pollution pathways. The results of MST markers agreed with those from 16S AmpSeq and the FEAST algorithm: humans were the main pollution source in the dry season, and ruminant and swine were the main pollution sources in the wet season at this river site near Beijing, China.…”
Section: In-depth Review Of the Application Areas Of Genetic Faecal P...mentioning
confidence: 99%